Pendidikan Multikultural Sebagai Wahana Pembentukan Karakter - Ida Zahara Adibah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Multiculturalism in UNDARIS is not only limited to cultural diversity, but also to various aspects especially related to education developed by religious lecturers as educators in tertiary institutions. Practical multiculturalism in question is the ability of lecturers and students in adapting themselves to the environment in which there are a variety of cultures, regions and religions. The most important element in character building is the mind, in which there are all programs that are formed from his life experience, is the forerunner of everything. This program then forms a belief system that can eventually form patterns of thinking that can influence his behavior. The awareness of differences in belief has increasingly been understood as a necessity, moreover driven by the condition that the difference becomes a beauty realized by lecturers and members of UNDARIS. Commitment to having the ability to capture differences is one vehicle for character building.